Nietzsche and the political - Conway, Daniel W. (Routledge, 1996)
In this study Daniel Conway shows how Nietzsche's political thinking bears a closer resemblance to the conservative republicanism of his predecessors than to the progressive liberalism of his contemporaries. The key contemporary figures such as Habermas, Foucault, McIntyre, Rorty and Rawls are also examined in the light of Nietzsche's political legacy. Nietzsche and the Political also draws out important implications for contemporary liberalism and feminist thought, above all showing Nietzsche's continuing relevance to the shape of political thinking today.